Planning a Multi‐site, Complex Intervention for Homeless People with Mental Illness: The Relationships Between the National Team and Local Sites in Canada's At Home/Chez Soi Project. Issue 3 (11th September 2012) - Nelson, Geoffrey; Macnaughton, Eric; Goering, Paula; Dudley, Michael; O'Campo, Patricia; Patterson, Michelle; Piat, Myra; Prévost, Natasha; Strehlau, Verena; Vallée, Catherine
Abstract: This research focused on the relationships between a national team and five project sites across Canada in planning a complex, community intervention for homeless people with mental illness called At Home/Chez Soi, which is based on the Housing First model. The research addressed two questions: (a) what are the challenges in planning? and (b) what factors that helped or hindered moving project planning forward? Using qualitative methods, 149 national, provincial, and local stakeholders participated in key informant or focus group interviews. We found that planning entails not only intervention and research tasks, but also relational processes that occur within an ecology of time, local context, and values. More specifically, the relationships between the national team and the project sites can be conceptualized as a collaborative process in which national and local partners bring different agendas to the planning process and must therefore listen to, negotiate, discuss, and compromise with one another. A collaborative process that involves power‐sharing and having project coordinators at each site helped to bridge the differences between these two stakeholder groups, to find common ground, and to accomplish planning tasks within a compressed time frame. While local context and culture pushed towards unique adaptations of Housing First, the principles of the Housing First model provided a foundation for a common approach across sites and interventions. The implications of the findings for future planning and research of multi‐site, complex, community interventions are noted.